Inner Methods and Outer Rites: An Exploration of Salvation Through Refinement in the Golden Writings on the Great Achievement of Deliverance by the Numinous Treasure of Highest Clarity - Hongyi Chen (Religions, 2025)
Salvation through Refinement (liandu 鍊度) is a distinctive Daoist rite aimed at rescuing the souls of the deceased from hell, enabling their rebirth, and ultimately facilitating their transcendence. The Golden Writings on the Great Achievement of Deliverance by the Numinous Treasure of Highest Clarity (Shangqing Lingbao Jidu Dacheng Jinshu 上清靈寶濟度大成金書), compiled by Zhou Side 周思得 (1359–1451), preserves a wealth of material related to Salvation through Refinement. This content can be divided into two parts: the ritual procedures of Salvation through Refinement and the associated internal practices (neishi 内事). Zhou explicitly stated that the Salvation through Refinement ritual originated from the Golden Book of Salvation according to the Lingbao Tradition (Lingbao Lingjiao Jidu Jinshu 靈寶領教濟度金書), compiled by Lin Lingzhen 林靈真 (1239–1302), whereas the internal practices are not attributed to any specific source. Comparative analysis confirms that the section on internal practices derives from the Brief Discussions of Inner Method of Taiji for Sacrificing to and Sublimating [the Souls of the Deceased] (Taiji Jilian Neifa Yilüe 太極祭鍊內法議略), compiled by Zheng Sixiao 鄭思肖 (1241–1318). Zheng Sixiao’s Salvation through Refinement method centers on Visualization and Actualization (cunxiang 存想), with the entire process taking place internally within the ritual master’s body. Building upon this foundation, Zhou Side incorporated additional ritualized actions and recitations, striving to integrate external ritual with internal practice. In doing so, he constructed a model of Salvation through Refinement characterized by the union of inner methods and outer rites. Inner Sublimation emerged during the Southern Song period, likely influenced in both principle and method by the then-prevalent School of the Mind (xinxue 心學). It sought to counter the increasing complexity of ritual practices at that time. Meanwhile, the continued practice of traditional forms of Retreats (zhai 齋) and Offerings (jiao 醮) reflected the Ming (1368–1644) rulers’ emphasis on the didactic function of such rituals. In his compilation, Zhou cited the views and materials of others under the name of Tian Sizhen 田思真 (fl. early 12th century) to articulate the inner meanings and core doctrines of the Numinous Treasure (lingbao 靈寶) rites. By positioning Tian Sizhen as an intermediary, Zhou not only established a line of transmission between the rites he compiled and the orthodox Numinous Treasure lineage represented by Lu Xiujing 陸修靜 (406–477) but also affirmed his conscious identification with the Daoist ritual tradition and his stance regarding its lineage.